Association between mesothelin expression and survival outcomes in patients with triple-negative breast cancer: a protocol for a systematic review. Issue 1 (December 2016) - Wang, Mei; Li, Aihua; Sun, Guangwen; Mbuagbaw, Lawrence; Reid, Susan; Lovrics, Peter; Thabane, Lehana
Abstract Background Mesothelin is a membrane-bound glycoprotein. Although the biologic function of mesothelin is not very clear, researchers have found that it plays a role in the survival, proliferation, and migration of tumor cells. Identified as a tumor-associated biomarker, mesothelin is more often overexpressed in triple-negative breast cancer (TNBC) than in common luminal breast tumor subtype or normal tissues. The objective of this review is to determine the association between the expression of mesothelin and overall survival in patients with TNBC. Methods/design We will search the following electronic databases: MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, and Web of Science with no time or language restriction. Prospective or retrospective longitudinal studies that investigate mesothelin expression in TNBC or the prognosis of TNBC with mesothelin baseline measurement will be selected. Two reviewers will independently assess every abstract or full text for inclusion. Data on clinical outcomes, as well as on study design, research setting, study population, demographic characteristics of the participants, and methodological quality, will be extracted using a structured codebook developed by the authors. A pooled measure of associations will be assessed through meta-analyses if appropriate. Heterogeneity across the included studies will be evaluated using theI 2 statistics. Findings will be reported according to the Meta-Analysis of Observational Studies in Epidemiology (MOOSE) guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The quality of evidence and risk of bias of the studies will be evaluated. Discussion The aim of this systematic review is to synthesize the evidence regarding the association between the expression of mesothelin and the survival outcomes of patients with TNBC. A better understanding of the expression frequency and prognostic value of mesothelin in TNBC will be essential to identifying a novel therapeutic target. Systematic review registration PROSPEROCRD42016036212